P Penentuan Nilai SPF (Sun Protection Factor) dan Evaluasi Fisik Sediaan Cream Ekstrak Etanol Bunga Rosella (Hibiscus sabdariffa L.) Sebagai Sun Protection - Melitia, Ni Putu Nova; Audina, Mia; Mahdiyah, Dede (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: The skin has a very influential role in protecting the body from the external environment such as physical impact or exposure to free radicals. Skin problems often occur due to exposure to sunlight in the form of ultraviolet (UV) rays. So to maintain healthy skin, you can use sunscreen cream preparations or sun protection. rosella flower (Hibiscus sabdariffa L.) contains anthocyanin compounds which are efficacious as antioxidants which have potential as sunscreens thatare able to absorb UV-A and UV-B rays thereby reducing the intensity on the skin.Objective: To observe and analyze the differences in the results of physical evaluation and the SPF value of variations in the concentration of the active substance in sunscreen cream preparations of ethanol extract of rosella flowers (Hibiscus sabdariffa L.) as sun protection.Methods: This research is a pre-experimental study with a one-shot case study design. Sunscreen cream is formulated with different active substance concentrations of rosella flower ethanol extract, namely 9%, 10%, 11%. The evaluation included organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesion, emulsion type and in vitro SPF activity test. Data were analyzed using one way ANOVA.Results: The results showed that the variation of the active substance affected the differences in the results of physical evaluation on pH, spreadability, adhesion and viscosity, as well as the SPF activity test. Based on one way ANOVA statistics, the results obtained were <0.05, meaning that there was an effect of variations in the concentration of the active substance of the ethanol extract of rosella flowers. SPF value activity gets (F1)29,12,(F2)29,97(F3)29,97 in the range of 30 SPFConclusion: The results of the physical evaluation and activity testing of the SPF value of the rosella flower ethanol extract sunscreen cream had a significant difference in the results from the influence of variations in the active substance.Keywords: Rosella flower, Sun cream